Antimicrobial dressing efficacy against mature Pseudomonas aeruginosa biofilm on porcine skin explants. Issue 4 (13th September 2013) - Phillips, Priscilla L; Yang, Qingping; Davis, Stephen; Sampson, Edith M; Azeke, John I; Hamad, Afifa; Schultz, Gregory S
Abstract An ex vivo porcine skin explant biofilm model that preserves key properties of biofilm attached to skin at different levels of maturity (0–3 days) was used to assess the efficacy of commercially available antimicrobial dressings and topical treatments. Assays were also performed on the subpopulation of antibiotic tolerant biofilm generated by 24 hours of pre‐treatment with gentamicin (120× minimal inhibitory concentration) prior to agent exposure. Five types of antimicrobial agents (iodine, silver, polyhexamethylene biguanide, honey and ethanol) and four types of moisture dressings (cotton gauze, sodium carboxymethylcellulose fibre, calcium alginate fibre and cadexomer beads) were assessed. Time‐release silver gel and cadexomer iodine dressings were the most effective in reducing mature biofilm [between 5 and 7 logarithmic (log) of 7‐log total], whereas all other dressing formulations reduced biofilm between 0·3 and 2 log in 24 or 72 hours with a single exposure. Similar results were found after 24‐hour exposure to silver release dressings using an in vivo pig burn wound model, demonstrating correlation between the ex vivo and in vivo models. Results of this study indicate that commonly used microbicidal wound dressings vary widely in their ability to kill mature biofilm and the efficacy is influenced by time of exposure, number of applications, moisture level and agent formulation (sustained release).